Nanoscale strategies: doxorubicin resistance challenges and enhancing cancer therapy with advanced nanotechnological approaches - Lim, Jian Xin; Yong, Yoke Keong; Dewi, Firli Rahmah Primula; Chan, Siok Yee; Lim, Vuanghao (Springer, 2025)
Doxorubicin (DOX), an anthracycline, is widely used in cancer treatment by interfering RNA and DNA synthesis. Its broad antitumour spectrum makes it an effective therapy for a wide array of cancers. However, the prevailing drug-resistant cancer has proven to be a significant drawback to the success of the conventional chemotherapy regime and DOX has been identified as a major hurdle. Furthermore, the clinical application of DOX has been limited by rapid breakdown, increased toxicity, and decreased half-time life, highlighting an urgent need for more innovative delivery methods. Although advancements have been made, achieving a complete cure for cancer remains elusive. The development of nanoparticles offers a promising avenue for the precise delivery of DOX into the tumour microenvironment, aiming to increase the drug concentration at the target site while reducing side effects. Despite the good aspects of this technology, the classical nanoparticles struggle with issues such as premature drug leakage, low bioavailability, and insufficient penetration into tumours due to an inadequate enhanced permeability and retention (EPR) effect. Recent advancements have focused on creating stimuli-responsive nanoparticles and employing various chemosensitisers, including natural compounds and nucleic acids, fortifying the efficacy of DOX against resistant cancers. The efforts to refine nanoparticle targeting precision to improve DOX delivery are reviewed. This includes using receptor-mediated endocytosis systems to maximise the internalisation of drugs. The potential benefits and drawbacks of these novel techniques constitute significant areas of ongoing study, pointing to a promising path forward in addressing the challenges posed by drug-resistant cancers.